From the listed options, it's A) y= 0.05
Like this if it helps-hope it does
Answer:
x = -6
Step-by-step explanation:
-7x+16=58
Subtract 16 from each side
-7x+16-16=58-16
-7x = 42
Divide by -7
-7x/-7 = 42/-7
x = -6
Answer:
x = -4
Step-by-step explanation:
Given: -2(4x + 4) - 3x - 2 = 34
To solve this equation, we have to isolate the variable. (Get x by itself).
We'll follow the PEMDAS rule as far as parentheses.
So, -2(4x + 4) - 3x - 2 = 34
= -8x - 8 - 3x - 2 = 34
Now, we have to get x by itself. To do this, we'll move the numbers without variables to the other side.
Hence:
-8x - 8 - 3x - 2 = 34
+8 +2 +8 +2
-8x - 3x = 34 + 8 + 2
Now, we'll simplify.
-11x = 44
Lastly, to rid the negative eleven from the x, we have to divide negative eleven by the rest of the equation.
-11x = 44
-------------
-11
x = -4
Answer:
y = 5
Step-by-step explanation:
Since this is an isosceles triangle, Angle B and Angle C are equivalent. We can use this to find x
3x = 75
x = 25
Angles in a triangle add up to 180, so knowing the measure of Angle B and Angle C, we can find the measure of Angle A
Angle A = 180-(75+75)
Angle A = 180-150
Angle A = 30
We know Angle A = 4y+10
4y + 10 = 30
4y = 20
y = 5